Residual Stress Analysis on Welded Joints by Means of Numerical Simulation and Experiments 2018
DOI: 10.5772/intechopen.72134
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Pattern Prediction in Spray Transfer Multipass Welding by Means of Numerical Simulation

Abstract: One of the main problems of gas metal arc welding (GMAW) process is the generation of residual stresses (RS), which has a direct impact on the mechanical performance of welded components. Nevertheless, RS pattern prediction is complex and requires the simulation of the welding process. Consequently, most of the currently used dimensioning approaches do not consider RS, leading to design oversized structures. This fact is especially relevant in big structures since it generates high material, manufacturing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Figure 3 shows the heat distribution determined in this study using FEM. Comparing against FE and experiment results of Esnaola et al [32], it can concluded that distribution and the maximum heat determined in the current study are close to FE result of Esnaola et al [32].…”
Section: Validation Of Fea For Residual Stress Analysis Due To Weldingsupporting
confidence: 86%
See 3 more Smart Citations
“…Figure 3 shows the heat distribution determined in this study using FEM. Comparing against FE and experiment results of Esnaola et al [32], it can concluded that distribution and the maximum heat determined in the current study are close to FE result of Esnaola et al [32].…”
Section: Validation Of Fea For Residual Stress Analysis Due To Weldingsupporting
confidence: 86%
“…In the present study, the coupled (two-way) method is employed for residual stress analysis of welding, and heat source is modelled as body flux on each weld component. To evaluate the accuracy of FEA for residual stress analysis a butt weld of Gas metal arc welding (GMAW) between two plates with dimensions of 200 × 10 mm is taken from the research work of Esnaola et al [32], which is shown in figure 1.…”
Section: Validation Of Fea For Residual Stress Analysis Due To Weldingmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, according to the welding speed and material addition discretization size, elements are reactivated (rebirthed) simulating the welding torch pass (Fig. 2) [15].…”
Section: Numerical Methodology For Residual Stress Estimationmentioning
confidence: 99%